ANALISIS KESULITAN SISWA PADA MATERI MATRIKS DI KELAS XI SMA SWASTA AL MAKSUM - Kairuddin; Ferdiansyah Rigani; Nuraidah Zahra; Pebi Fauziyana Br Tarigan; Agnia Kamila Rambe; Lutfiah Syahrawani Siregar (Universitas Nias Raya, 2025)
This study aims to investigate the difficulties experienced by students in understanding matrix material, with a particular focus on matrix multiplication. The research was conducted with 13 students from grade XI of Al Maksum Private High School Medan. To obtain comprehensive data, researchers used a combination of interviews and written tests. These instruments were designed to explore students’ conceptual understanding as well as the procedural aspects of solving matrix problems. The data collected were then analyzed using the Miles and Huberman model, which involves three key steps: data reduction, data display, and drawing conclusions. The results of the analysis revealed that students encountered various obstacles in learning matrices, especially in performing matrix multiplication. The main difficulties stemmed from several factors, including a lack of understanding of the basic concepts and rules that govern matrix operations, particularly multiplication. Additionally, many students made calculation errors, especially when dealing with positive and negative numbers. Some students also demonstrated low confidence in their answers, which may have led them to second-guess correct solutions. Moreover, insufficient attention to detail when performing step-by-step calculations often resulted in inaccurate final answers. These findings highlight the importance of reinforcing conceptual understanding, improving arithmetic accuracy, and building students’ confidence through targeted instructional strategies and practice. Such improvements may help students overcome their current learning obstacles in matrix-related topics.